Green Transformational Leadership and Green Voice Behavior: The Motivational Role of Green Psychological Empowerment - Sarah Rietze; Franziska Schölmerich; Clara Kühner; Hannes Zacher (Corporate Social Responsibility and Environmental Management, 2025)
Improving organizational environmental performance requires broad, proactive employee engagement. Company leaders can play an important role in motivating employees to speak up on environmental issues in the workplace. Drawing on self-concept and psychological empowerment theories, we propose and test a model that examines how perceived green transformational leadership is associated with employees' green psychological empowerment and, in turn, employees' green voice behavior. We conducted a two-wave survey study with 170 participants. Results of structural equation modeling showed that green transformational leadership was positively related to all four dimensions of green psychological empowerment—green meaning, competence, self-determination, and impact. Additionally, green transformational leadership was indirectly associated with green voice behavior via green meaning and impact. This research contributes to the literature by introducing green psychological empowerment as a new construct to explain the motivational pathways between green transformational leadership and green voice behavior.
Keywords: 650; employee green behavior; environmental sustainability; green psychological empowerment; green transformational leadership; green voice behavior